2014
DOI: 10.5009/gnl13374
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Microsomal Triglyceride Transfer Protein Can Predict the Response to Antiviral Therapy in Egyptian Patients with Chronic Hepatitis C Virus Genotype 4 Infection

Abstract: Background/AimsA polymorphism in the microsomal triglyceride transfer protein (MTP) is associated with hepatic fibrosis, and carriers showed higher levels of steatosis, higher levels of hepatitis C virus (HCV) RNA and advanced fibrosis. The aim of this study was to study MTP expression pattern in HCV patients and impact of the MTP polymorphism on the response to antiviral therapy.MethodsOne hundred consecutive naive HCV genotype 4 patients were recruited to receive antiviral therapy, and 40 control subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Sub-group-analysis by prospective and retrospective studies showed similar SVR rates: 53% (CI: 50–56%) in forty-three prospective studies[10, 11, 1316, 18, 27, 28, 34, 3842, 46, 48, 53–56, 62, 63, 6567, 69, 72, 73, 7578, 80, 81, 83, 84, 88, 90, 91, 93, 95, 96] and 53% (CI: 46–59%) in eight retrospective studies[12, 35, 37, 45, 59, 71, 79, 85]. Significant heterogeneity was observed in both sub-group analyses with I 2 >50% (Figure 4).…”
Section: Resultsmentioning
confidence: 95%
“…Sub-group-analysis by prospective and retrospective studies showed similar SVR rates: 53% (CI: 50–56%) in forty-three prospective studies[10, 11, 1316, 18, 27, 28, 34, 3842, 46, 48, 53–56, 62, 63, 6567, 69, 72, 73, 7578, 80, 81, 83, 84, 88, 90, 91, 93, 95, 96] and 53% (CI: 46–59%) in eight retrospective studies[12, 35, 37, 45, 59, 71, 79, 85]. Significant heterogeneity was observed in both sub-group analyses with I 2 >50% (Figure 4).…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, the GG and GT genotypes were considered independent protective factors against steatosis in patients with chronic hepatitis C and HCV genotype 1 and non-1 [32]. Finally, Saad et al [9] also studied this polymorphism, although not in relation to steatosis, and they reported an association between the GT and TT genotypes and severe fibrosis and cirrhosis ( P  = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…The function of MTTP is related to the assembly and secretion of low-density lipoproteins (LDLs), such as very low-density lipoproteins (VLDLs) [5, 8, 9]. A functional SNP in the promoter region of MTTP (−493G/T) has been found to play an important role in the regulation of gene expression and influences the concentration of circulating LDL in the plasma of healthy individuals [10].…”
Section: Introductionmentioning
confidence: 99%